2014
DOI: 10.1093/geronb/gbu046
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of the Effects of Early Influences and Midlife Characteristics on Successful Aging

Abstract: Objectives. Previous research revealed that successful aging includes both objective and subjective dimensions. This longitudinal analysis examines how early life influences and midlife characteristics predict stability and change in successful aging over a 4-year period. Method. Data from 3,379 people living in New Jersey who completed baseline telephone interviews between 2006 and 2008 and follow-up mail surveys in 2011 were analyzed. Latent profile analysis identified people who aged successfully according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 49 publications
4
40
1
3
Order By: Relevance
“…In an extension of this work, longitudinal follow up of the cohort permitted examining earlier life characteristics and later life behaviors as they predict stability and change in successful aging prospectively. Gender, race, education, never marrying and incarceration (earlier life characteristics) as well as midlife status (currently married, working), health behaviors (smoking, drinking, BMI, exercise), and social support distinguished people who continued to age successfully four years later from those who did not (Pruchno & Wilson-Genderson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In an extension of this work, longitudinal follow up of the cohort permitted examining earlier life characteristics and later life behaviors as they predict stability and change in successful aging prospectively. Gender, race, education, never marrying and incarceration (earlier life characteristics) as well as midlife status (currently married, working), health behaviors (smoking, drinking, BMI, exercise), and social support distinguished people who continued to age successfully four years later from those who did not (Pruchno & Wilson-Genderson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All but one study focused on older populations, those aged 70+ and often in 85 to 90+ individuals. Puchno et al found that midlife predictors of healthy ageing differed from those which apply later in life (25). In addition, it appears that some biomarkers of ageing which appear robust in younger old individuals may not be valid in very old people.…”
Section: Discussionmentioning
confidence: 99%
“…Pruchno et.al.) suggesting that maintenance of healthy ageing at follow up was more common among men, those who were working, the married, and those having better social relationships at baseline (25). …”
Section: Current Evidence On Operationalisation Of Definitions Of Heamentioning
confidence: 99%
“…The few studies that have examined resilience and successful aging together have conceptualized resilience as a personality characteristic predictive of successful aging (Jeste et al, 2013;Wagnild, 2003), yet this approach belies the perspective that resilience is a dynamic process. Recent longitudinal studies have depicted successful aging as a process (Andrews, Clark, & Luszcz, 2002;Hsu & Jones, 2012;Morack, Ram, Fauth, & Gerstorf, 2013;Pruchno & Wilson-Genderson, 2014), but these studies have not adequately examined the role of personality. Our understanding of the role played by personality vis-a-vis resilience and successful aging is in its infancy.…”
Section: Differences Between Resilience and Successful Agingmentioning
confidence: 99%